Towards the Problem of Forming Full Strength Welded Joints on Aluminum Alloy Sheets. Part I: AA2024; AIP Conference Proceedings; Vol. 1783 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures 2016 - Fortuna S. Sergey; Eliseev A. Alexander; Kalashnikova T. Tatiana; Kolubaev Е. А. Evgeny Aleksandrovich (2016, 2016)
Title screen